2021
DOI: 10.1021/acs.energyfuels.1c00561
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Byproducts from Hydrothermal Liquefaction of Sewage Sludge and Manure: the Development of a Struvite-Producing Unit for Nutrient Recovery

Abstract: Hydrothermal liquefaction (HTL) presents a promising technology to recover energy from sewage sludge and manure as bio-crude oil. The liquid and solid phases after HTL are considered as byproducts; however, the latter is rich in nutrients, which offers a possibility for nutrient recovery and manufacturing of valuable products. This study focuses on the simultaneous recovery of phosphate and ammoniacal nitrogen as struvite by combining the liquid HTL byproduct and leachate from the solid HTL byproduct. To imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…In addition, micronutrients such as Fe, Cu, Zn or Co were detected. However, small amounts of toxic or dangerous agricultural compounds, such as Cr, As or Hg, were also present [28,41].…”
Section: Struvite Precipitation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, micronutrients such as Fe, Cu, Zn or Co were detected. However, small amounts of toxic or dangerous agricultural compounds, such as Cr, As or Hg, were also present [28,41].…”
Section: Struvite Precipitation Experimentsmentioning
confidence: 99%
“…Both treatments require the addition of Mg and, through aeration, achieve CO2 stripping to reach a slightly basic pH (8-8.5) which causes the spontaneous precipitation of struvite in the presence of ammonium [24][25][26]. At the laboratory scale, phosphorus recovery as struvite was studied in a liquid effluent after WO treatment of municipal sewage sludge [27,28], process similar to the applied in this work.…”
Section: Introductionmentioning
confidence: 99%
“…As for the land application of biosolid residuals from anaerobic digestion biosolids for plant fertilizers, bioavailability of the nutrients in HTL solids was found to be lower than that of the sewage sludge feedstock and simultaneously demonstrated that heavy metal content in the solids exceeded the threshold values for use as a fertilizer . However, recovery of low bioavailable phosphorus has also been demonstrated using HTL solids and other residuals to recover between 42 and 92% as struvite. , Struvite, a crystalline mineral of ammonia, magnesium, and phosphate (NH 4 MgPO 4 ·6H 2 O), can be directly used as a slow-release inorganic fertilizer, helping to reduce fertilizer runoff and the consumption of fertilizers. Several companies offer struvite recovery from digester effuents with full-scale systems operational throughout the US.…”
Section: Overview Of Potential Valorization Optionsmentioning
confidence: 99%
“…39 However, recovery of low bioavailable phosphorus has also been demonstrated using HTL solids and other residuals to recover between 42 and 92% as struvite. 39,40 Struvite, a crystalline mineral of ammonia, magnesium, and phosphate (NH 4 MgPO 4 •6H 2 O), can be directly used as a slow-release inorganic fertilizer, helping to reduce fertilizer runoff and the consumption of fertilizers. Several companies offer struvite recovery from digester effuents with full-scale systems operational throughout the US.…”
Section: Optionsmentioning
confidence: 99%
“…Solids from HTL carry around 100 kg of carbon from single feedstock processing, however this number was reduced to 56 kg in the combined approach. The solids from HTL of agricultural waste streams are rich in phosphorus [45], and further processing is needed to retrieve fertilizergrade forms of this element [46]. Thus, the reduction of carbon yielded as solids in the HTL process can also be beneficial for the handling and valorization of this fraction, greatly benefiting agricultural management of land and soil nutrient circularity.…”
Section: Process Carbon Balancementioning
confidence: 99%